Black female college athletes' perception of power in sport and society. Issue 1 (2nd January 2017) - Carter-Francique, Akilah R.; Dortch, Deniece; Carter-Phiri, Khrystal
ABSTRACT: The purpose of this study was to examine Black female college athletes' perception of power within the context of a "safe cultural space". Scholars note the ability to discern the notion of power and its dynamics is a key factor towards empowerment. For marginalized populations, addressing topics such as power is best within a safe cultural space, or an environment that is free from surveillance and allows students to freely express themselves (Collins, P. (2000). Black feminist thought: Knowledge, consciousness, and the politics of empowerment (2nd ed.). New York, NY: Routledge.). Employing Black feminist thought, eleven ( N = 11) Black female collegiate athletes that participated in a culturally relevant program within a historically White institution of higher education were examined utilizing qualitative methods. Findings revealed the women's understanding of power was as a possessive attribute; and, the words and symbols they attributed to power reflected hegemonic examples of power. Hegemonic ideologies pervade college athletics, thus, the creation of "safe cultural spaces" allowed the Black female college athletes to acknowledge their marginalization amongst peers and discern how power dynamics affects their development in sport and society.